Landesman-Lazer type conditions for a system of p-Laplacian like operators - Amster, P. (2007)
We study the existence of periodic solutions for a nonlinear second order system of ordinary differential equations of p-Laplacian type. Assuming suitable Nagumo and Landesman-Lazer type conditions we prove the existence of at least one solution applying topological degree methods. We extend a celebrated result by Nirenberg for resonant systems. © 2006 Elsevier Inc. All rights reserved.